Software design to simulate FMCW radar signal: a case study of INDERA - Sediono, Wahju; Lestari, Andrian Andaya (2010)
Nowadays computer simulation plays a significant role in analyzing the radar signals. The research group at the Radar and Communication Systems (RCS) has developed a maritime radar, called INDERA, that works using the Frequency Modulated Continuous Wave (FMCW) technology. In line with the enhancement of the radar system we have alsodeveloped a software system that is able to be used for simulating the FMCW signal of radar INDERA. This work presents a design of the software that can be utilized not only to generate and analyze the FMCW radar signal, but also reconstruct the received radar signal onto a PPI (Plan Position Indicator) radar display. The software tool completed here will help us in analyzing the actual radar returns as well as the effects of surface scattering. The gained knowledge about the system characteristics in response to the abruptly changing situations is of great importance in extracting range information more easily.